2012
DOI: 10.1111/j.1745-4549.2012.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON OF SUPERCHILLING AND FREEZING ON THE MICROSTRUCTURE, MUSCLE QUALITY AND PROTEIN DENATURATION OF GRASS CARP (CTENOPHARYNGODON IDELLUS )

Abstract: Quality changes in grass carp during superchilled storage at −2C were evaluated in terms of the microstructure, drip loss, pH value, total volatile basic nitrogen (TVB‐N), trimethylamine nitrogen (TMA‐N), water holding capacity (WHC), salt soluble protein (SSP) and Ca2+‐ATPase activity by comparison with frozen storage at −18C. The microstructure of grass carp muscle was seriously damaged with the exhibition of myofibril shrinkage and breakage under frozen storage. Both TVB‐N and TMA‐N contents in superchilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Our results are similar of the finding of Mi [37] which reported for controlled both TVB-N and TMA-N contents in super chilled grass carp under the acceptable values within 21 days of storage. Those authors Mi [37] suggested the super chilling of grass carp attenuated the denaturation of myofibrillar protein and the damage of muscle structure associated with freezing, where extractability of salt soluble protein and Ca 2+ -ATPase activity were reduced. A shelf life of 21 days for super chilled could be estimated by the overall quality evaluation.…”
Section: Ph Valuesupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are similar of the finding of Mi [37] which reported for controlled both TVB-N and TMA-N contents in super chilled grass carp under the acceptable values within 21 days of storage. Those authors Mi [37] suggested the super chilling of grass carp attenuated the denaturation of myofibrillar protein and the damage of muscle structure associated with freezing, where extractability of salt soluble protein and Ca 2+ -ATPase activity were reduced. A shelf life of 21 days for super chilled could be estimated by the overall quality evaluation.…”
Section: Ph Valuesupporting
confidence: 82%
“…Similar to our results, Shen [34] found that after 11 days of storage at -3°C TVB-N and other freshness indicators (TAC, K value, sensory scores) were relatively low. Mi [37], and Liu [39] reach to similar conclusions studying on the total volatile basic nitrogen (TVB-N), and trimethylamine nitrogen (TMA-N) in whole ungutted and filleted grass carp (Ctenopharyngodon idellus) during super chilled storage at -2°C to -3°C. Those authors concluded that TVB-N and TMA-N can be controlled under the acceptable values within 21 days.…”
Section: Total Volatile Base Nitrogenmentioning
confidence: 52%
“…This result was in accordance with the findings that for grass carp subjected to superchilling and freezing. [21] The initial decrease may be explained by the accumulation of lactic acid from anaerobic glycolysis and the production of inorganic phosphate due to ATP degradation, [32] whereas rising pH value during the later period of storage may be associated with decomposition of amino compounds resulting from microbial and autolytic reactions. [33] In the initial 3 days, the pH of samples superchilled at −3°C with tea polyphenols decreased slower than that frozen at −18°C and superchilling at −3°C, which indicated that tea polyphenols may interact with oxidase proteins and reduce their activity, inhibiting the rate of pH reduction due to glycolysis and ATP degradation.…”
Section: Changes Of Phmentioning
confidence: 99%
“…[ 21] A 10 g sample was homogenised with 90 mL 0.6 mol/L perchloric acid solution, and the resulting suspension was centrifuged at 3000 r/min for 10 min at 4°C using a high-speed bench centrifuge (TGL-16G, Shanghai Anheng scientific instrument factory, Shanghai, China). A 10 mL supernatant was distilled and titrated in an automatic Kjeldahl Apparatus (Kjeltec2300, Foss, Sweden) with the blank experiment of 10 mL perchloric acid solution.…”
Section: Total Volatile Base Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation